2013
DOI: 10.1002/adfm.201203686
|View full text |Cite
|
Sign up to set email alerts
|

The Exfoliation of Graphene in Liquids by Electrochemical, Chemical, and Sonication‐Assisted Techniques: A Nanoscale Study

Abstract: The different exfoliation routes of graphite to produce graphene by sonication in solvent, chemical oxidation and electrochemical oxidation are compared. The exfoliation process and roughening of a flat graphite substrate is directly visualized at the nanoscale by scanning probe and electron microscopy. The etching damage in graphite and the properties of the exfoliated sheets are compared by Raman spectroscopy and X‐ray diffraction analysis. The results show the trade‐off between exfoliation speed and preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(175 citation statements)
references
References 31 publications
(41 reference statements)
5
170
0
Order By: Relevance
“…[56][57][58] The penetration of oxidizing agents might again cause augmented oxidation of the graphite resulting in an increasing amount of ketone groups accompanied by hydroxyl groups. [58][59][60] Recently, Deheryan et al 61 reported that the magnitude of the capacitive currents can be correlated with θ for carbon nanosheets. Thus it is expected that C dl measured for the BPPs is directly coupled to the specific surface area of graphite, which was in contact with the sulfuric acid during CV measurement.…”
Section: Resultsmentioning
confidence: 99%
“…[56][57][58] The penetration of oxidizing agents might again cause augmented oxidation of the graphite resulting in an increasing amount of ketone groups accompanied by hydroxyl groups. [58][59][60] Recently, Deheryan et al 61 reported that the magnitude of the capacitive currents can be correlated with θ for carbon nanosheets. Thus it is expected that C dl measured for the BPPs is directly coupled to the specific surface area of graphite, which was in contact with the sulfuric acid during CV measurement.…”
Section: Resultsmentioning
confidence: 99%
“…The effi cient intercalation as well as gas eruption promote the separation of graphene sheets from neighboring graphene layers. [ 23 ] Moreover, water is crucial for the overall exfoliation process, as it not only serves as a solvent to decrease the viscosity of the solution, but also produces reactive oxygen-containing species from anodic oxidation, which in turn corrode the graphite anode at grain boundaries or edges, facilitating SO 4 2− intercalation. [ 24 ] However, in acidic electrolytes, the ion intercalation is so fast that it occurs simultaneously with exfoliation at all graphite edges, in contrast to the ideal model, where graphene layers peel off layer by layer individually.…”
Section: Research Newsmentioning
confidence: 99%
“…By monitoring the structural deformation at the graphite interface, Palermo et al have proven that effi cient intercalation and bubble formation inside graphite interlayers are important factors governing fast and complete exfoliation. [ 23 ] In practice, exfoliation begins at any part of graphite and these stages do not occur in order, which is the main reason for the wide distribution of graphene layers. There seems to be a trade-off between the effi ciency of exfoliation and the preservation of graphene quality.…”
Section: Understanding Of the Exfoliation Mechanismmentioning
confidence: 99%
“…Several liquids were used to create stable dispersions of graphene such as surfactants in aqueous media, ionic liquids and organic solvents. [10][11][12][13][14][15] The organic solvent ortho-dichlorobenzene (o-DCB), being aromatic, is able to interact with graphene via π -π stacking. o-DCB has a surface tension of 36.6 mJ/m 2 , which is very close to the proposed range (40-50 mJ/m 2 ).…”
Section: Introductionmentioning
confidence: 99%